(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The reality of Life shows that today’s intense period also requires the formation of political consciousness and legal literacy in young people. It must be admitted that today non-governmental media, in particular, internet sites, as well as online channels hosted by bloggers, are in the leading positions in audience coverage and content ratings in general. We will only be happy about these achievements of them. Alternatively, it also means that we still have a lot to do in front of us. In this article, feedback and feedback will be made on the analysis of the state of development of the electronic database of periodicals.